Thermal rating monitoring of the TNB overhead transmission line using line ground clearance measurement and weather monitoring techniques - Rahim A.A.; Abidin I.Z.; Tarlochan F.; Hashim M.F. (2023)
Power transfer through a short transmission line is mainly limited by thermal rating. Accurate determination of thermal rating can maximize power transfer which subsequently saves utility from building new lines. Thermal rating normally is set to a certain conductor temperature which during operation the transmission line will not has problem with ground clearance and the conductor material properties will remain in its original state. The conductor temperature varies with weather parameters and loading and it has close relationship with line sag or line ground clearance. The conductor temperature can be determined by monitoring the line ground clearance and weather parameters and the actual thermal rating can be calculated. Monitoring of the line ground clearance can be done in real time using laser distance measurement sensor with data logger and real time monitoring and calculation software. 2010 IEEE.